Characterization and dissolution test of recrystallized mefenamic acid by fast cooling methods - Rasydy, La Ode Akbar; Damayanti, Hilda; Satrio, Erza; Supriyanta, Jaka (Pharmaciana, 2025)
Mefenamic acid, classified as a Biopharmaceutics Classification System (BCS) Class II drug, exhibits high permeability but low dissolution rates, limiting its bioavailability. This study aims to enhance the dissolution rate of mefenamic acid through crystal structure modification using fast cooling recrystallization with three distinct solvents: acetone (AMA), ether (AMEt), and ethyl acetate (AME). The recrystallized crystals were characterized using advanced techniques, including polarized microscopy, X-ray Diffraction (XRD), Fourier Transform Infrared (FTIR) spectroscopy, and Differential Scanning Calorimetry (DSC), alongside solubility and dissolution testing. Recrystallization yielded crystals with varied morphologies and sizes, achieving high crystal yields of 92.66% (AMA), 85.54% (AMEt), and 94.59% (AME). FTIR analysis revealed that AME crystals exhibited stronger OH bonding, indicated by the highest peak intensity. XRD diffractograms demonstrated distinct peak patterns at specific 2θ positions for AME crystals, suggesting internal structural changes (polymorphism) while maintaining identical chemical composition. DSC thermograms further confirmed variations in melting points between recrystallized crystals and pure mefenamic acid. Dissolution tests revealed that recrystallized mefenamic acid exhibited significantly improved solubility and dissolution rates compared to its pure form. These findings highlight that rapid cooling recrystallization can produce mefenamic acid polymorphs with optimized dissolution properties, potentially enhancing its pharmacological performance and also provides a promising approach to improving the bioavailability of poorly soluble drugs, offering significant implications for pharmaceutical formulation development.